Using a Transradial Method, The Results of Primary Percutaneous Coronary Intervention at a Tertiary Care Cardiac Centre - Nasir Khan, Habib Ul Haq, Sarfraz Hussain Sahito, Syed Zain Raza Naqvi, Shahzad Majeed Bhatti, Waqqas Ishaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to investigate the in-hospital outcomes of primary percutaneous coronary intervention (PCI) performed using a transradial technique in a cardiac centre that provides tertiary care. Study Design: Descriptive/ observational study Place and Duration: Department of cardiology, Peshawar Institute of Cardiology, Hayatabad phase 5 Peshawar, KPK in the duration from April, 2022 to September, 2022. Methods: 104 patients were included in the trial; all had ST-segment elevation myocardial infarction and had presented within 12 hours of symptom onset without a history of thrombolytic treatment, coronary angioplasty, or cardiac surgery. Patients were monitored for forearm hematoma and mortality during their hospital stays after diagnostic angiography and primary percutaneous coronary intervention (PCI) of the artery supplying the infarct.SPSS 24.0 was used to analyze all data. Results: There were majority 75 (72.1%) males and 29 (27.9%) females among all cases. Included patients had mean age 48.44±13.67 years and had mean BMI 27.6±3.48 kg/m2. 48 (46.2%) patients were smokers and most common comorbidity was diabetes found in 63 (60.6%) cases followed by HTN, CAD, hyperlipidemia and obesity. Success rate of PCI by using transradial method was found in 101 (97.1%) cases. Mortality was only found in 2 cases and post-procedure forearm hematoma was found in 1 patients. Mortality and forearm hematoma was found because of old age among patients. Conclusion: In this study, we came to the conclusion that primary percutaneous coronary intervention (PCI) performed using a transradial technique is a viable alternative that has great success rates in terms of both mortality rates and morbidity, such as hematoma of the forearm. Keywords: Primary percutaneous coronary intervention, transradial approach, Forearm hematoma, mortality